2019
DOI: 10.1371/journal.pone.0208754
|View full text |Cite
|
Sign up to set email alerts
|

Social responses of travelling finless porpoises to boat traffic risk in Misumi West Port, Ariake Sound, Japan

Abstract: Anthropogenic effects have created various risks for wild animals. Boat traffic is one of the most fatal risks for marine mammals. Individual behavioral responses of cetaceans, including diving behavior such as changing swimming direction and lengthing inter-breath interval, to passing boats is relatively well known; however, the social function of cetacean responses to boat traffic in a natural setting remains poorly understood. We focused on describing the behavioral responses of single and aggregated finles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Notwithstanding, VTOL UAVs are an excellent platform for aerial studies of marine mammals, having been used in studies of morphometrics, behaviour, demographics and relative abundance [6][7][8][9][10][11][12]. While many of these studies have focused on pinnipeds [2,10,11], others have also focused on cetaceans including humpback whales (Megaptera novaeangliae) [13,14]; grey whales (Eschrichtius robustus) [15]; southern right whales (Eubalaena australis) [16]; blue (Balaenoptera musculus), fin (B. physalus) and sperm (Physeter macrocephalus) whales [17]; killer whales (Orcinus orca) [12]; bottlenose dolphins (Tursiops truncatus) [18]; dusky dolphins (Lagenorhynchus obscurus) [7] and finless porpoise (Neophocaena asiaeorientalis) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, VTOL UAVs are an excellent platform for aerial studies of marine mammals, having been used in studies of morphometrics, behaviour, demographics and relative abundance [6][7][8][9][10][11][12]. While many of these studies have focused on pinnipeds [2,10,11], others have also focused on cetaceans including humpback whales (Megaptera novaeangliae) [13,14]; grey whales (Eschrichtius robustus) [15]; southern right whales (Eubalaena australis) [16]; blue (Balaenoptera musculus), fin (B. physalus) and sperm (Physeter macrocephalus) whales [17]; killer whales (Orcinus orca) [12]; bottlenose dolphins (Tursiops truncatus) [18]; dusky dolphins (Lagenorhynchus obscurus) [7] and finless porpoise (Neophocaena asiaeorientalis) [19].…”
Section: Introductionmentioning
confidence: 99%
“…UAVs have been used to carry out ethological studies related to social relationships [48,50,67,102], collaborative hunting [65] and foraging behaviours [33][34][35]47], kinematic studies and movement patterns [28,32,76,143], respiratory dynamics [93], energy expenditure and behavioural events involving mother-calf pairs [29,50,51], the effects of micropredators [30,75], the impact of swimmer approaches during in-water tourism activities [45], responses to boat traffic [100], responses to sound playback experiments [73], responses to the presence of naval sonar in military training areas [131,132], responses to pinger exposure [69], and comparisons with simultaneous underwater acoustic recordings [68,77].…”
Section: Behavioural Studiesmentioning
confidence: 99%
“…A distance of 100 m was used, as it greatly reduces the influences of the presence and cavitation noise of the research vessel on the acoustic detection of porpoises and dolphins. Previous studies have reported that finless porpoises and humpback dolphins may avoid vessels (Ng & Leung 2003, Li et al 2008, Morimura & Mori 2019, Piwetz et al 2021. The detection range of the A-tag was ~450 m, based on the sound intensity and propagation of the clicks emitted by dolphins and porpoises (Fisher & Simmons 1977, Fang et al 2015.…”
Section: Field Workmentioning
confidence: 99%